Spread of Unethical Behavior in Organizations: A Dynamic Social Network Perspective - Zuber, Franziska (Journal of business ethics, 2015)
The spread of unethical behavior in organizations has mainly been studied in terms of processes occurring in a general social context, rather than in terms of actors’ reactions in the context of their specific social relationships. This paper introduces a dynamic social network analysis framework in which this spread is conceptualized as the result of the reactions of perpetrators, victims, and observers to an initial act of unethical behavior. This theoretical framework shows that the social relationships of the actors involved in an initial act impact in multiple ways the likelihood that unethical behavior spreads. It reveals furthermore that social relationships may change in the wake of unethical behavior, such that indirect negative consequences can arise for organizations. The proposed framework provides a basis for the development of a formal stochastic actor-oriented model of network dynamics which would enable simulations of the spread of unethical behavior.